Searching social networks - Bharath Vijay Palukurthi. (2012)
In the wake of the recent information revolution, there has been a strong interest in understanding the structure of real world social networks and in detecting cohesive subcomponents within social networks. These models to detect cohesion are gaining popularity in Social Network Analysis. These models have found usage in diverse areas ranging from analyzing friendship networks such as Facebook to understanding criminal networks such as terrorist rings, etc.